2016
DOI: 10.1021/acs.chemrev.6b00532
|View full text |Cite
|
Sign up to set email alerts
|

Acetalated Dextran: A Tunable and Acid-Labile Biopolymer with Facile Synthesis and a Range of Applications

Abstract: Acetalated dextran (Ac-DEX) is a tunable acid-labile biopolymer with facile synthesis, aptly designed for the formulation of microparticles for vaccines and immune modulation. Tunability of degradation is achieved based on the kinetics of reaction and the molecular weight of the parent dextran polymer. This tunability translated to differential rates of activation of CD8+ T cells in an in vitro ovalbumin model and illustrated that acid-labile polymer can activate CD8+ T cells at an increased rate compared to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(111 citation statements)
references
References 62 publications
5
105
0
Order By: Relevance
“…The degradation rate of the polymeric NPs in a cell-free environment was studied since it directly influences the release kinetics of the drug from the NP core. According to the literature, Acdex is an acid-labile polymer with a considerably higher pH sensitivity compared to the PLGA polymer [17,31]. Our results revealed that after Furthermore, at pH 4.8 after 50 min, the Acdex NPs degraded by only about 30%, whereas the Acdex[BRP-187] NPs degraded by 75% ( Fig.…”
Section: Degradation Profile Of the Nanoparticlessupporting
confidence: 64%
See 2 more Smart Citations
“…The degradation rate of the polymeric NPs in a cell-free environment was studied since it directly influences the release kinetics of the drug from the NP core. According to the literature, Acdex is an acid-labile polymer with a considerably higher pH sensitivity compared to the PLGA polymer [17,31]. Our results revealed that after Furthermore, at pH 4.8 after 50 min, the Acdex NPs degraded by only about 30%, whereas the Acdex[BRP-187] NPs degraded by 75% ( Fig.…”
Section: Degradation Profile Of the Nanoparticlessupporting
confidence: 64%
“…The properties of PLGA are influenced by the ratio of lactic to glycolic acid units, with a 50:50 composition showing the fastest degradation [16]. An alternative to PLGA is acetalated dextran (Acdex), a recently developed dextran derivative offering favorable properties as carrier for drugs with low solubility [17]. Acdex is composed of acyclic and cyclic acetal groups, with the acyclic acetals degrading faster than the cyclic acetal groups [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consideration of biocompatibility and biodegradation, natural materials like polysaccharides and proteins are optimal choices to fabricate all kinds of carriers on account of natural biodegradation and excellent biocompatibility [19][20][21][22][23][24][25][26]. Therefore, pH-sensitive natural polysaccharides have been designed and synthesized through reversible acetylation, which also endow materialhydrophobic groups [27][28][29][30][31][32][33]. The hydrophilic-lipophilic characteristic of polysaccharides is simultaneously altered by acetylation, which benefits the O/W emulsion method for nanoparticle fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophilic-lipophilic characteristic of polysaccharides is simultaneously altered by acetylation, which benefits the O/W emulsion method for nanoparticle fabrication. The pH response property of acetylated materials is attributed to the transition of undissolvable hydrophobic acetal groups to dissolvable hydrophilic hydroxy groups in pH 5.5 aqueous solution [27][28][29][30][31][32][33]. In our previous work, pH-sensitive β-cyclodextrin (β-CD) was synthesized and investigated concerning the effects of reaction condition on pH responsiveness and stability [33].…”
Section: Introductionmentioning
confidence: 99%